IMPLEMENTASI MANAJEMEN KOMUNITAS BELAJAR DALAM PEMBINAAN KOMPETENSI PEDAGOGIK GURU DI SD NEGERI 44 PONTIANAK BARAT - Rivaie, Lia Hizriani; Hairida, Hairida; Rosnija, Eni; Sulistyarini, Sulistyarini; Sanulita, Henny (Universitas Tanjungpura, 2026)
Teacher learning communities are a form of sustainable professional development that play a strategic role in improving teachers’ pedagogical competence. This study aims to describe the implementation of learning community management in fostering teachers’ pedagogical competence at SD Negeri 44 Pontianak Barat. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews, passive participant observation, and document analysis. Research informants included the principal, the learning community coordinator, and teachers. Data analysis followed the stages of data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. The findings indicate that the management of the learning community has been implemented in accordance with management functions, namely planning, organizing, implementing, and supervising. The implementation contributes to improving lesson planning, student-centered learning, and reflective teaching practices. Keywords: Educational Management, Professional learning community, Pedagogical Competence. Abstrak Komunitas belajar guru merupakan strategi pengembangan profesional berkelanjutan yang berperan penting dalam peningkatan kompetensi pedagogik guru. Penelitian ini bertujuan untuk mendeskripsikan implementasi manajemen komunitas belajar dalam pembinaan kompetensi pedagogik guru di SD Negeri 44 Pontianak Barat. Penelitian menggunakan pendekatan kualitatif deskriptif. Teknik pengumpulan data dilakukan melalui wawancara mendalam, observasi partisipan pasif, dan studi dokumentasi. Informan penelitian meliputi kepala sekolah, ketua komunitas belajar, dan guru. Analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan dengan triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa manajemen komunitas belajar telah dilaksanakan sesuai fungsi perencanaan, pengorganisasian, pelaksanaan, dan pengawasan serta berkontribusi pada pembinaan kompetensi pedagogik guru. Kata Kunci: Manajemen Pendidikan, Komunitas Belajar, Kompetensi Pedagogik